2023
DOI: 10.1002/adma.202209181
|View full text |Cite
|
Sign up to set email alerts
|

An Active Pixel‐Matrix Electrocaloric Device for Targeted and Differential Thermal Management

Abstract: CPU) moved into multi-core, coolers can deal with the chip as a single-site heat source for effective cooling. But the multi-core CPU is packaged as a whole, and the localized overheating site in one core can heat others up. The localized overheating site makes the thermal challenge much more difficult, and it caused more than 55% of all failures in current electronics. [5,6] As operating temperature approaches 70-80 °C, the performance of electronics will degrade by ≈10% for every 2 °C increase. [7] So, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Although an outside electric supply was previously required to power the EC device to achieve the effective thermal management reported in the literature ( 35 37 , 43 ), we demonstrated that the EC device can instead be powered directly on site by an integrated flexible OPV module. The integrated device shows the same outstanding performance, including the same temperature difference (Δ T ) at the same electric field (Fig.…”
Section: Temperature Span Of the Oetc System In Different Working Sce...mentioning
confidence: 81%
See 3 more Smart Citations
“…Although an outside electric supply was previously required to power the EC device to achieve the effective thermal management reported in the literature ( 35 37 , 43 ), we demonstrated that the EC device can instead be powered directly on site by an integrated flexible OPV module. The integrated device shows the same outstanding performance, including the same temperature difference (Δ T ) at the same electric field (Fig.…”
Section: Temperature Span Of the Oetc System In Different Working Sce...mentioning
confidence: 81%
“…The working mechanism of the OETC system for the cooling mode (Fig. 2B) is the same as that powered by the electric supply ( 37 ), but in our system, we power it directly by the electricity generated by the OPV module (see fig. S9 for details).…”
Section: Working Mechanism Of the Oetc System In Cooling/warming Modementioning
confidence: 99%
See 2 more Smart Citations
“…( C ) Δ T span as a function of EC temperature change (Δ T EC ) of different EC-based prototypes. BTO, BaTiO 3 ( 29 32 ); PVDF, poly(vinylidene fluoride-trifluoroethylene) [P(VDF-TrFE)] ( 33 ) and poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) [P(VDF-TrFE-CFE)] ( 12 , 34 , 35 ); BST@PVDF, Ba x Sr 1– x TiO 3 nanoparticles-filled P(VDF-TrFE-CFE) ( 36 , 37 ); PMN-PT, 0.9Pb(Mg 1/3 Nb 2/3 )O 3 –0.1PbTiO 3 ( 38 ); PST, PbSc 0.5 Ta 0.5 O 3 ( 15 , 39 , 40 ).…”
Section: Optimized Regenerationmentioning
confidence: 99%